A New Signal Estimator from the NIR Detectors of the Euclid Mission. (5th September 2016) - Kubik, Bogna; Barbier, Remi; Chabanat, Eric; Chapon, Arnaud; Clemens, Jean-Claude; Ealet, Anne; Ferriol, Sylvain; Gillard, William; Secroun, Aurelia; Serra, Benoit; Smadja, Gerard; Tilquin, André
Abstract: We describe how the Euclid detectors in the Near Infrared Spectrometer and Photometer (NISP) channel will be read out on board and present an analytic expression for the estimated fluence in each pixel with the associated quality factor of the fit per pixel. The method accounts for the Poisson like distribution of the data and includes the effects of noise correlations that arise after the coadding procedure of frames read non-destructively up the ramp during one exposure. The bias of the flux estimator presented in this paper is kept lower than 0.3% over a wide rang of scientifically interesting fluxes of Euclid. The associated error is by 6% lower than the commonly used formula derived in Rauscher et al. in the context of an equally weighted least squares fit. Moreover, the quality factor follows the very well known χ th 2 ( x ; n ) distribution and thus provides a well behaved statistical tool to check the goodness of the ramp fit. The method is proposed in the context of a large amount of data per exposure, produced by the NISP detectors, that cannot be transferred to the ground for the subsequent processing. The method, which is validated using real and simulated test data, can be safely used by most near-infrared instruments which require very accurate measurements to be performed on board.